2013
DOI: 10.4081/hls.2013.e12
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for pre-eclampsia among women at antenatal booking in Kano, Northern Nigeria

Abstract: Pre-eclampsia (PE) is an important cause of maternal mortality. There have been several studies on risk factors assessment with conflicting reports across the globe on this disease; however, rigorous recent evaluation of these factors is uncommon in this region. The aim of the present study was to determine the risks factors in the early-onset PE in Aminu Kano Teaching Hospital (AKTH), Kano (Northern Nigeria). We conducted a case-control study in Nigeria between April 2009 and January 2010 to identify the risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Increased age of women is an important risk factor probably due to increased villous reaction leading to pre-eclampsia in a woman greater than 30years, as has been found in other studies. [13][14][15] Age of menarche at 12 years was found to be a significant risk factor for Preeclampsia (OR=2.59; 1.53-4.40), similar to finding of Ramesh et al 4 (2014). Early menarche (≤12 y) has been associated with increased risk of CVD events in other studies potentially mediated by increased adiposity associated with early menarche.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Increased age of women is an important risk factor probably due to increased villous reaction leading to pre-eclampsia in a woman greater than 30years, as has been found in other studies. [13][14][15] Age of menarche at 12 years was found to be a significant risk factor for Preeclampsia (OR=2.59; 1.53-4.40), similar to finding of Ramesh et al 4 (2014). Early menarche (≤12 y) has been associated with increased risk of CVD events in other studies potentially mediated by increased adiposity associated with early menarche.…”
Section: Discussionsupporting
confidence: 84%
“…[11][12][13][14][15] The factors that have been postulated to influence the risk of pre-eclampsia in various studies include Diabetes and Gestational Diabetes, 12-14-16-18 Obesity, 19 Multiple pregnancy. 17,18 Personal and family history of pre-eclampsia, 20 chronic infections, 21 UTI, 2 First pregnancy and Older maternal age or Younger than 20 years age, 2 Renal disease and autoimmune disorder, 16,17 prolonged interval between pregnancies [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and History of abortion 8 and maternal diet. 22 Rationale: Knowledge and identification of sociodemographic and clinical risk factors for PE will help in estimating each woman's individualized risk and allow antenatal surveillance to be directed at these women and guide the healthcare providers for counseling of such women and possibly reduce the recurrence risk of PE if some modifiable risk factors (like obesity) are present.…”
Section: Introductionmentioning
confidence: 99%
“…This is in keeping with genetic factors being implicated in the development of preeclampsia where daughters of women with preeclampsia are about four times more likely to develop the disease than daughter in-laws and it has been established that it is familial. 4,19 This study reported a significantly higher mean serum uric acid level amongst participants with preeclampsia than in those without preeclampsia. This increased amount of serum uric acid amongst clients with preeclampsia has been reported by several studies and this increased amount is thought to correlate with the severity of the disease condition.…”
Section: Discussionmentioning
confidence: 61%
“…6,-15-17 Coming to Addis Ababa, pre-eclampsia increased from 2.2% in 2009 to 5.58% in 2013. 18 As the report of the previous studies, factors associated with pre-eclampsia were classified as socio-demographic, 12,-19-24 obstetric, [19][20][21][23][24][25][26] and clinical factors. 21,22,26,27 The result of this study is important for improving the quality-of-life and survival status of mothers and newborn babies and for social-capital and sustainable economic growth of the country at large.…”
Section: Introductionmentioning
confidence: 99%
“… 6 ,– 15–17 Coming to Addis Ababa, pre-eclampsia increased from 2.2% in 2009 to 5.58% in 2013. 18 As the report of the previous studies, factors associated with pre-eclampsia were classified as socio-demographic, 12 ,– 19–24 obstetric, 19–21 , 23–26 and clinical factors. 21 , 22 , 26 , 27 …”
Section: Introductionmentioning
confidence: 99%